2021
DOI: 10.1111/phn.12956
|View full text |Cite
|
Sign up to set email alerts
|

Exploring women's perspectives on prenatal screening for adverse childhood experiences

Abstract: Objective: To learn more about women's views on screening for adverse childhood experiences (ACEs) during healthcare visits in pregnancy.Design: Mixed methods with an online survey. Sample:A convenience sample of 154 women with a history of one or more pregnancies was recruited through public health department social media pages in one predominantly rural region of a Midwest state.Measurements: Quantitative measures included demographic variables, ACE scores, and preferences regarding screening format, strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 21 publications
(28 reference statements)
1
19
0
Order By: Relevance
“…The overall finding that women accepted routine trauma discussion masks several complexities and contradictions. In eight studies, women reported feeling unprepared for the discussion and found it intrusive [32,33,[35][36][37][38][39]42]. This was reflected by a woman who was interviewed in the study by Millar et al (2021) [35]:…”
Section: 'I Did Not Know How To Say It and No-one Asked Me': Should M...mentioning
confidence: 99%
See 3 more Smart Citations
“…The overall finding that women accepted routine trauma discussion masks several complexities and contradictions. In eight studies, women reported feeling unprepared for the discussion and found it intrusive [32,33,[35][36][37][38][39]42]. This was reflected by a woman who was interviewed in the study by Millar et al (2021) [35]:…”
Section: 'I Did Not Know How To Say It and No-one Asked Me': Should M...mentioning
confidence: 99%
“…Participants in 14 studies expressed that they felt routine trauma discussion is acceptable and worthwhile [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. One of the participants in the study undertaken by Montgomery, Seng and Chang (2021) [36] proposed: "It might have just put a thought in my head, even if it wasn't something that I shared with anybody, it might have just put a thought in my head which might have been useful at some point" [36].…”
Section: 'I Did Not Know How To Say It and No-one Asked Me': Should M...mentioning
confidence: 99%
See 2 more Smart Citations
“…A TIC initiative can include asking about past and current traumatic experiences, which has been subject to debate in the literature (Finkelhor, 2018;McLennan et al, 2020;McLennan et al, 2019). Although most patients would feel comfortable discussing their ACEs with their healthcare provider (Flanagan et al, 2018;Olsen et al, 2021;Purkey et al, 2018), many healthcare providers do not incorporate asking about ACEs in their routine medical practice or feel comfortable discussing ACEs with their patients (Tink et al, 2017;Weinreb et al, 2010). A quantitative study conducted with 145 obstetrics and gynecology fellows found that less than 30% of physicians spoke to their patients about childhood trauma (Farrow et al, 2018).…”
Section: Introductionmentioning
confidence: 99%